Hundred top-cited articles focusing on acute kidney injury: a bibliometric analysis. Issue 7 (27th July 2016) - Liu, Yuan-hui; Wang, Sheng-qi; Xue, Jin-hua; Liu, Yong; Chen, Ji-yan; Li, Guo-feng; He, Peng-cheng; Tan, Ning
Abstract : Background: Acute kidney injury (AKI) is a major global health issue, associated with poor short-term and long-term outcomes. Research on AKI is increasing with numerous articles published. However, the quantity and quality of research production in the field of AKI is unclear. Methods and analysis: To analyse the characteristics of the most cited articles on AKI and to provide information about achievements and developments in AKI, we searched the Science Citation Index Expanded for citations of AKI articles. For the top 100 most frequently cited articles (T100), we evaluated the number of citations, publication time, province of origin, journal, impact factor, topic or subspecialty of the research, and publication type. Results: The T100 articles ranged from a maximum of 1971 citations to a minimum of 215 citations (median 302 citations). T100 articles were published from 1951 to 2011, with most articles published in the 2000s (n=77), especially the 5-year period from 2002 to 2006 (n=51). The publications appeared in 30 journals, predominantly in the general medical journals, led by New England Journal of Medicine (n=17), followed by expert medical journals, led by the Journal of the American Society of Nephrology (n=16) and Kidney International (n=16). The majority (83.7%) of T100 articles were published by teams involving ≥3 authors. T100 articles originated from 15 countries, led by the USA (n=81) followed by Italy (n=9). Among the T100 articles, 69 were clinical research, 25 were basic science, 21 were reviews, 5 were meta-analyses and 3 were clinical guidelines. Most clinical articles (55%) included patients with any cause of AKI, followed by the specific causes of contrast-induced AKI (25%) and cardiac surgery-induced AKI (15%). Conclusions: This study provides a historical perspective on the scientific progress on AKI, and highlights areas of research requiring further investigations and developments.